Identification of Mosses (Bryophytes) in The Curug Silawe Area Magelang Regency and Their Connection to Environmental Elements - Ainisya, Umi Nur; Wijayanti, Erna (Fakultas Biologi Universitas Jenderal Soedirman, 2024)
Bryophytes are a group of low-level plants that grow widely and are found in tropical areas. Their distribution is influenced by biotic and abiotic factors such as water, light, temperature, humidity, and altitude. The ecological role of lichens in tropical ecosystems is to maintain water balance, nutrient cycling, bioindicators of environmental change, open space for other plants, and carbon sinks on peatlands. The role of moss is very important for the ecosystem, and there is no data on moss species in the Silawe waterfall area, so researchers conducted this study to identify environmental factors that affect moss diversity. Data collection for moss plants was carried out through a combination of exploration and field observation methods. Based on the results of observations, 7 species of moss, 5 leaf mosses (Bryopsida), and 2 liverworts (Marchantiopsida) were obtained. The identified ferns came from 7 different families, namely Funariaceae, Dicranaceae, Fissidentaceae, Hypnaceae, Entodontaceae, Marchantiaceae, and Lepidoziaceae. The identified moss species were Funaria hygrometrica, Dicranum fuscescens, Fissidens sp., Hypnum cupressiforme, Entodon sp., Marchantia polymorpha, and Bazzania sp.